2020
DOI: 10.3389/fcell.2020.00244
|View full text |Cite
|
Sign up to set email alerts
|

Novel Aspects of Extracellular Vesicles in the Regulation of Renal Physiological and Pathophysiological Processes

Abstract: Extracellular vesicles (EV) are nanosized particles released by a large variety of cells. They carry molecules such as proteins, RNA and lipids. While urinary EVs have been longer studied as a source of biomarkers for renal and non-renal disorders, research on EVs as regulatory players of renal physiological and pathological processes has experienced an outbreak recently in the past decade. In general, the microenvironment and (patho)physiological state of the donor cells affect the cargo of the EVs released, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Extracellular vesicles (EVs) such as exosomes are important mediators of cell-cell communication that act by transmitting proteins and genetic information. Vesicles incorporate molecules from their origin cells containing proteins, nucleic acids and lipids (Rigalli et al, 2020). A recent study demonstrated that exosomes are produced in renal proximal tubular epithelium following various fibrotic injury (UUO, ischemia/reperfusion or Liu, 2010;Lee and Nelson, 2012;LeBleu et al, 2013 Partial EMT Concept of partial EMT TECs expressed both markers of epithelial and mesenchymal cells while remained attached to the basement membrane during fibrosis.…”
Section: Role Of Extracellular Vesical Communication In the Kidney Inmentioning
confidence: 99%
“…Extracellular vesicles (EVs) such as exosomes are important mediators of cell-cell communication that act by transmitting proteins and genetic information. Vesicles incorporate molecules from their origin cells containing proteins, nucleic acids and lipids (Rigalli et al, 2020). A recent study demonstrated that exosomes are produced in renal proximal tubular epithelium following various fibrotic injury (UUO, ischemia/reperfusion or Liu, 2010;Lee and Nelson, 2012;LeBleu et al, 2013 Partial EMT Concept of partial EMT TECs expressed both markers of epithelial and mesenchymal cells while remained attached to the basement membrane during fibrosis.…”
Section: Role Of Extracellular Vesical Communication In the Kidney Inmentioning
confidence: 99%
“…The pattern of perfusion parameters (flow and resistance) and the measurement of biomarkers such as neutrophil gelatinase lipocalin, liver fatty acid binding protein and inflammatory cytokines (IL‐6, IL‐8, IL‐18) could be helpful in determining the level of injury and in predicting outcome in these cases and for more prolonged periods of NMP. Recently reported new biomarkers, such as extracellular vesicles, microRNAs, and nanoparticles derived from blood/urine or imaging technologies to assess the microcirculation could be applied to assess viability during NMP in the future 45,46 …”
Section: Viability Assessmentmentioning
confidence: 99%
“…Extracellular vesicles (EVs) refer to the membrane structures released by all types of cells through different biogenic pathways ( 120 ). EVs are intercellular messengers that are involved in a wide range of physiological and pathological processes ( 121 ). EVs have the advantages of exhibiting stable physical and chemical properties ( 122 ).…”
Section: Macrophage-sensing Mediators In Akimentioning
confidence: 99%
“…In addition, blocking the exosome-mediated transfer of miR-23a between RTECs and macrophages may be an innovative method for enhancing renal tubulointerstitial inflammation. In summary, exosomes are involved in adjusting the routine function of the kidney, as well as in promoting and inhibiting various pathophysiological reactions ( 121 ).…”
Section: Macrophage-sensing Mediators In Akimentioning
confidence: 99%